Ebonex supported iridium as anode catalyst for PEM water electrolysis. (21st September 2015) - Slavcheva, Evelina; Borisov, Galin; Lefterova, Elefteria; Petkucheva, Elitsa; Boshnakova, Iveta
Abstract: The work presents a research on the preparation and properties of iridium dispersed on Magnelli phase titania by sol gel method. The material is characterised in regard to morphology, surface structure and electronic state, electrochemical performance, and catalytic activity toward the oxygen evolution reaction in view of its application as anode in polymer electrolyte membrane water electrolysis. The results obtained are discussed in comparison to the previously studied magnetron sputtered iridium oxide anodes. They show a need for improvements concerning the Ir/Ebonex active surface area and catalyst utilisation. At the same time, the performed accelerated durability tests demonstrate excellent stability of the synthesized composite catalyst and enhanced resistance to corrosion. Highlights: Ebonex-supported Ir is investigated as anode catalyst in PEM water electrolysis. Its OER catalytic efficiency is comparable to that of sputtered iridium oxide films. The performed accelerated tests demonstrate high stability to degradation. The calculated morphology factor shows a need for increase in catalyst utilization.